2015
DOI: 10.11648/j.ajep.20150405.14
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Stock Analysis Along Altitudinal Gradient in Gedo Forest: Implications for Forest Management and Climate Change Mitigation

Abstract: Forests provide important ecological and environmental benefits. They serve as natural sinker of atmospheric CO 2 to mitigate climate change. In Ethiopia although, there is significant forest resource, the studies on carbon stock potential and factors that affect this potential have not been well studied. This study was done with the aim of estimating carbon stock potential and related factors that affect carbon sequestration in Gedo forest. Data was collected from 10m x 20m plot along transect in systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
6
17
3
5
Order By: Relevance
“…The average AGC (116.46 t C ha −1 ) of the current finding is greater than tropical (45.45 t C ha −1 ) and regional (58.9 t C ha −1 ) estimates [43,92]. On the other hand, all recently assessed forests in Ethiopia exhibited higher aboveground, root, and litter carbon stock compared to the finding of the current study [87][88][89][90][91]. The status of the forest and its composition of species, along with climatic and edaphic factors, might be responsible for the differences in aboveground, root, and litter carbon stock.…”
Section: Biomass Carbon Stockcontrasting
confidence: 58%
See 1 more Smart Citation
“…The average AGC (116.46 t C ha −1 ) of the current finding is greater than tropical (45.45 t C ha −1 ) and regional (58.9 t C ha −1 ) estimates [43,92]. On the other hand, all recently assessed forests in Ethiopia exhibited higher aboveground, root, and litter carbon stock compared to the finding of the current study [87][88][89][90][91]. The status of the forest and its composition of species, along with climatic and edaphic factors, might be responsible for the differences in aboveground, root, and litter carbon stock.…”
Section: Biomass Carbon Stockcontrasting
confidence: 58%
“…The presence of SOC in lower soil depths indicates how these layers of the soil are important pools in terms of preserving soil organic carbon for a long time [86]. Unlike studies elsewhere in Ethiopia [87][88][89][90][91], the current study yielded high SOC in the natural forest.…”
Section: Soil Carbon Stockmentioning
confidence: 52%
“…According to the total carbon, the current study result was relatively greater than that of some of the reported carbon stock studies of Ethiopian forests; Mount Zequalla forest (Girma et al, 2014) and Humbo forest (Chinasho et al, 2015) (Table 7). However, the present result is smaller to that of Egdu forest (Yohannes et al, 2015) and Tara Gedam forest (Gedefaw, 2015) ( Table 7). Nevertheless, the current study carbon stock result was more or less similar toAdaba-Dodola and Danaba Community forest Bazezew et al,2014;Bazezew et al, 2015) (Table 7).The variation might be due to the variation of the age of the plants, existing species,and management of the forests (Bazezew et al, 2015).…”
Section: Carbon Stored In Each Individual Plant Speciescontrasting
confidence: 87%
“…Similarly, below ground biomass carbon stock in the studied area followed the same manner since it was a direct factor of above ground biomass (Brown, 2002). Bazezew et al,2014) 278.03 41.76 1.06 186.4 507.29 Danaba CF (Bazezew et al, 2015) 278.03 41.76 1.06 186.4 507.29 Egdu forest (Yohannes et al, 2015) 278.08 55.62 3.47 277.6 614.72 Humbo forest (Chinasho et al, 2015) 30.77 14.46 12.55 168.2 225.98 MauntZequalla forest (Girma et al, 2014) 273.2 47.6 6.5 57.6 348.8 Tara Gedam forest (Gedefaw, 2015) 306.66 61.52 0.9 274.3 643.11 Shawo forest (current study) 321.29 64.1 1.69 127.4 514.68 AGBC and BGBC-above ground and below ground biomass carbon stock; TCS-total carbon stock; LHDsBC-litter, herbs and grasses biomass carbon; CF-community forest…”
Section: Carbon Stored In Each Individual Plant Speciesmentioning
confidence: 63%
“…On the other hand, lower altitude is more prone to arable land due to gentle slope nature made to coexist less plant species. Yohannes et al (2015) conclude that, mountain forest mostly affects by environmental variables due to change in species structure and composition.Species evenness did not show a strong response to slope gradient as there is no significant difference in its value in all the three slope gradients (P>0.05). This indicates that the distribution of species in the natural vegetation was not affected by slope.…”
Section: Species Diversity and Evennessmentioning
confidence: 83%